The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/ps.1974
|View full text |Cite|
|
Sign up to set email alerts
|

Mosquito repellents: a review of chemical structure diversity and olfaction

Abstract: Research on mosquito chemical repellents continues to advance, along with knowledge of mosquito olfaction and behavior, mosquito-host interactions and chemical structure. New tools and technologies have revealed information about insect olfactory mechanisms and processing, providing a more complex approach for the interpretation of how chemical repellents influence host-seeking and feeding behavior. Even with these advances, there is still a large amount of information contained in the early works on insect re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 107 publications
0
57
0
4
Order By: Relevance
“…Documented attempts of deterring hematophagous insects date back to antiquity. Among the earliest reports of repellent use are from Herodotus, a Greek historian [17]. His account of communities burning plants to prevent the aggregation of biting flies demonstrates the success of this strategy.…”
Section: A Brief History Of Repellentsmentioning
confidence: 99%
“…Documented attempts of deterring hematophagous insects date back to antiquity. Among the earliest reports of repellent use are from Herodotus, a Greek historian [17]. His account of communities burning plants to prevent the aggregation of biting flies demonstrates the success of this strategy.…”
Section: A Brief History Of Repellentsmentioning
confidence: 99%
“…A simultaneous activation of different receptor sites may account for the high repellent effect of the ternary blend. Electrophysiological and molecular approaches, in fact, showed that repellents interact with olfactory and gustatory receptors in mosquito modulating their function through multiple molecular mechanisms (Paluck et al 2010;Bohbot et al 2011;Dickens and Bohbot 2013). Moreover, all three aldehydes tested in this study are perceived by the peripheral olfactory system of adult S. granarius males and females (Germinara et al 2002).…”
Section: Discussionmentioning
confidence: 75%
“…Clearly the nepetalactone molecule has spurred new interest and efforts in development of natural, alternative repellents. A recent review of insect repellents has been published (19).…”
Section: Discussionmentioning
confidence: 99%